TRANSFER PRICING AS A MODERATING VARIABLE OF THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON COMPANY PERFORMANCE - Lidyah, Rika; Hardiansyah; Eljawati; Sri Wahyuni Nur; Feryansyah (ITB AAS Indonesia Surakarta, 2025)
Abstract This research is a quantitative study with an explanatory approach, namely an approach that uses previous research as the main material to analyze more deeply and prove the hypothesis used in this study. The data used in this study are primary data that researchers obtained from Cemerlang Jaya bvangunan employees spread throughout Indonesia. The data obtained is in the form of an online questionnaire with a total of 10 questions related to the hypothesis in this study. The result in this article show show that the two hypotheses proposed by the researcher can be accepted due to similar answers from Cemerlang Jaya building employees spread throughout Indonesia who agree that good corporate governance can affect company performance, can improve employee welfare, and make the company's financial condition stable. Based on the results of the first row of the third table above, it shows that the influence of Good Corporate Governance on Company Performance can have a positive relationship direction and a significant influence because the value is positive and below the significance level of 0.05, namely 0.03. In addition, in the next row, the Transfer Pricing variable can also influence the Good Corporate Governance variable on Company Performance.because of the same thing, namely the P-Values ​​are positive and below the significance level of 0.05. This is because Transfer Pricing can affect the company's financial stability which ultimately has an impact on Company Performance. Keywords : Company Performance , of Good Corporate Governance , Transfer Pricing